2004
DOI: 10.1111/j.1540-8159.2004.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Implantable Cardioverter Defibrillator Use in Elderly Patients:

Abstract: This article addresses the feasibility and safety of ICD therapy in patients >80 years of age. Recent trials have expanded the indication for ICD implantation to include an increasing number and variety of patients. The feasibility of ICD implantation in elderly patients has not been adequately studied. A prospectively collected single center ICD database was analyzed to assess the safety and feasibility of ICD implantation in elderly patients. Patients were divided based on age into two groups (group 1: 70-79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…More recently, Noseworthy and colleagues [21] examined ICD related complications and survival in 29 octogenarians compared to 183 patients aged 70 to 79 years at the time of ICD implant. Noseworthy et al [21] found no significant differences in the complication rate between both age groups with a perioperative mortality of 0% in both age groups.…”
Section: Cohort Studies Of Elderly Icd Recipientsmentioning
confidence: 98%
“…More recently, Noseworthy and colleagues [21] examined ICD related complications and survival in 29 octogenarians compared to 183 patients aged 70 to 79 years at the time of ICD implant. Noseworthy et al [21] found no significant differences in the complication rate between both age groups with a perioperative mortality of 0% in both age groups.…”
Section: Cohort Studies Of Elderly Icd Recipientsmentioning
confidence: 98%
“…In one retrospective study stratifying patients at 65 years of age [29], there was no difference in length of hospital stay after ICD implantation in patients younger or older than 65 years of age. In another retrospective analysis of patients at least 70 years of age receiving ICDs, the complication rate was 6.6% in patients ages 70 to 79 years versus 13.1% in those older than 80 years of age (not statistically signifi cant) [19]. In a database of 31,000 Medicare ICD recipients, 10.8% had one or more complications during their hospital stay for ICD implantation [30•].…”
Section: Procedures Complicationsmentioning
confidence: 99%
“…Retrospective data regarding ICDs in octogenarians was analyzed in those receiving ICDs for secondary prevention [19]. This single-center database compared short-term survival among different age groups (183 patients ages 70-79 years and 29 patients > 80 years).…”
Section: Implantable Cardioverter Defi Brillators: Data In the Elderlymentioning
confidence: 99%
“…One single center experience with ICD therapy in patients greater than 80 years of age showed at least clinical equivalency between 183 septuagenarians and 29 octogenarians in survival, cause-specific mortality, and procedural complications over a 17-year retrospective review. 57) Another retrospective review reported that in a comparison between 74 patients greater than 75 years of age and 695 younger patients who had all undergone ICD implantation, there was no difference in the incidence of appropriate ICD defibrillations between the two groups. 58) Although this study reported that advanced age was the most powerful predictor of adverse outcomes, the incidence of sudden cardiac death was rare in the elderly ICD group.…”
Section: Device-based Therapymentioning
confidence: 99%